BELAJAR MEMBACA DENGAN METODE MONTESSORI - Faradiba Sari Harahap (Universitas Pahlawan Tuanku Tambusai, 2022)
For early childhood children, the ability to read is complex and detailed. In contrast to the ability to speak which can be obtained naturally from their surroundings, the ability to read must be learned with certain methods. Montessori is a children's education method that can optimize children's potential through learning that involves children's sensory and motor aspects in a detailed and fun way. This article is written to explain how early childhood children learn to read using the Montessori method. This research is a qualitative descriptive research. This research method is library research through data collection techniques obtained through books, journals, articles and other supporting sources. The results of this study explain that in the Montessori method, early childhood learns to read in two stages, namely the pre-reading stage and the technical stage of reading. At the Pre-Reading Stage, children can carry out activities such as talking, singing, listening to stories and reading aloud. At the Technical Stage of Reading, children learn to read through letter sounds or phonics using Sand Paper Letters and Movable Alphabet, building words using Object Boxes and Reading boxes, improving reading skills with Word lists, reading silently using Secret Box, introduced to phrases and sentences, understanding the concept of Subject - Predicate - Object - Description, and finally learning to read books. Keywords: Learning, Reading, Montessori Method